A new species of the genus Taikona Arita & O. Gorbunov, 2001 from Vietnam (Lepidoptera: Sesiidae) - Gorbunov, Oleg G.; Arita, Yutaka (Zootaxa, 2019)
A new clearwing moth species is described and illustrated from South Vietnam: Taikona ikedai sp. nov. The type series is deposited in the collection of the National Museum of Nature and Science, Tsukuba (formerly Natural Science Museum Tokyo). The female and the larval host plant are unknown. The genus Taikona was previously unrecorded in the country.